2013
DOI: 10.1002/ajpa.22445
|View full text |Cite
|
Sign up to set email alerts
|

Missing defects? A comparison of microscopic and macroscopic approaches to identifying linear enamel hypoplasia

Abstract: Linear enamel hypoplasia (LEH), the presence of linear defects of dental enamel formed during periods of growth disruption, is frequently analyzed in physical anthropology as evidence for childhood health in the past. However, a wide variety of methods for identifying and interpreting these defects in archaeological remains exists, preventing easy cross-comparison of results from disparate studies. This article compares a standard approach to identifying LEH using the naked eye to the evidence of growth disrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 28 publications
2
40
0
1
Order By: Relevance
“…These findings are contrary to a number of other bioarchaeological studies which have found that LEH are significantly associated with reduced longevity Duray, 1996;Stodder, 1997;DeWitte and Wood, 2008). Studies which use microscopic methods to identify abnormal perikymata routinely find a greater number of defects per tooth, in addition to a greater number of affected individuals than traditional macroscopic methods (King et al, 2005;Temple, 2014;Hassett, 2014). Macroscopic studies of LEH have been criticized by Goodman and Rose (1990), who suggest that simple irregularities in the surface of the crown may be mistaken for hypoplastic defects and that true hypoplasia can only be distinguished microscopically.…”
Section: Linear Enamel Hypoplasiamentioning
confidence: 65%
See 2 more Smart Citations
“…These findings are contrary to a number of other bioarchaeological studies which have found that LEH are significantly associated with reduced longevity Duray, 1996;Stodder, 1997;DeWitte and Wood, 2008). Studies which use microscopic methods to identify abnormal perikymata routinely find a greater number of defects per tooth, in addition to a greater number of affected individuals than traditional macroscopic methods (King et al, 2005;Temple, 2014;Hassett, 2014). Macroscopic studies of LEH have been criticized by Goodman and Rose (1990), who suggest that simple irregularities in the surface of the crown may be mistaken for hypoplastic defects and that true hypoplasia can only be distinguished microscopically.…”
Section: Linear Enamel Hypoplasiamentioning
confidence: 65%
“…High socioeconomic status did not protect infants and young children from episodes of stress, as individuals buried in the wealthy suburban cemetery of Chelsea Old Church displayed the highest crude prevalence of LEH (60%) when compared with individuals from both St. Benet Sherehog (39%) and the low status cemeteries (52%). Alternatively, a more conscientious approach to the recording of macroscopic LEH, such as that advised by Hassett (2014), may assist with the interpretation of macroscopic findings. Individuals buried at Chelsea Old Church included apothecaries, vintners, brewers and carpenters, as well as a number of residents who worked in the market gardens that surrounded the parish (Russett and Pocock, 2004;Cowie et al, 2008).…”
Section: Linear Enamel Hypoplasiamentioning
confidence: 99%
See 1 more Smart Citation
“…L'utilisation de la variation de l'espacement entre deux périkymaties et du degré minimal d'expression du défaut de l'émail comme indicateurs d'une hypoplasie font l'objet de nombreux débats (e.g. Hillson et Bond, 1997 ;Cunha et al, 2004 ;Hassett, 2014 Goodman et Rose (1990). Schematic illustration of longitudinal section of a modern humans lower canine, modified from Goodman and Rose (1990). considérons, comme Cunha et al, 2004, qu'une hypoplasie est présente s'il y a une réduction de l'épaisseur de l'émail, accompagnée ou non d'une différence marquée de la distance entre deux périkymaties, et que le niveau minimal d'altération de la surface dentaire reste arbitraire.…”
Section: Matériel Dentaire Et Méthodesunclassified
“…For example, new research is challenging our traditional interpretation of non-specific indicators of stress as measures of health status (Reitsema and McIlvaine 2014), including dental enamel defects (Hassett 2014;Hubbard et al 2009), periosteal reaction (e.g., DeWitte 2014a, 2014bDeWitte and Wood 2008;Weston, 2008Weston, , 2009Weston, , 2012, and porotic hyperostosis (McIlvaine 2013;Piperata et al 2014), as well as specific patterns of pathology that are diagnostic of metabolic conditions such as scurvy (Crandall and Klaus 2014) and anemia (Smith-Guzman 2015), and infections such as leishmaniasis (Marsteller et al 2011). The study of disease progression over the life course also is being examined more broadly in contemporary studies of paleopathology that also draw upon medical sources (e.g., Baker and Bolhofner 2013).…”
Section: Contemporary Directionsmentioning
confidence: 99%